Quantum-trajectory simulations of a two-level atom cascaded to a cavity QED laser - Abdul Hadi, Muhammad Salihi; Wahiddin, Mohamed Ridza; Hassan, Torla (American Physical Society, 2003)
We use the quantum theory of cascaded open systems to calculate the transmitted photon flux for a weak beam of photons from a cavity QED laser strongly focused onto a single, resonant two-state atom in the narrow-bandwidth limit. We study the dependence of the transmitted flux on the quantum statistics of the incident light. Both bunched and antibunched light generated by the microlaser are considered as input. Working within and outside the semiclassical perturbative regime, we explicitly demonstrate that the normalized transmitted photon flux may coincide with the second-order correlation function of the incident bunched light, but not for incident antibunched light both of which are generated by a cavity QED laser. Interestingly, the thresholdless cavity QED laser is ideal for investigating statistical saturation effects by virtue of its small system size and the large quantum fluctuations accompanying it. It has the advantage of characterizing to a certain extent the quantum noise responsible for the statistical saturation. One can also easily vary the degree of antibunching of the incident light by manipulating the pumping rate of the laser.